Effective depreciation model for commercial vehichles in Malaysia / Lim Alan, Krishna Moorthy Manicka and Theresa Wong Lai Har. - Lim, Alan; Manicka, Krishna Moorthy; Wong Lai Har, Theresa Lai Har (Accounting Research Institute (ARI), 2017)
Malaysian Financial Reporting Standards (MFRS) offers a choice for corporations to select their preferable depreciation methods to allocate the cost of the assets every year. Findings shown that majority of the corporations apply Straight Line method in depreciation calculation nowadays. However, Straight Line method is unable to show the fair value of the assets and received major criticism from past researchers. Hence, current research has applied a newly proposed method to conduct the depreciation calculation with the secondary data collected with the three existing accounting depreciation models. The net book value result was compared against the market value, and the analysis showed that newly proposed method could produce the closest proportion to the market value of the vehicles, and hence it is determined as the most effective depreciation model that can best reflect the current value of the motor vehicles.